Forecasting the potential of weak lensing magnification to enhance LSST large-scale structure analyses - Mahony, C; Fortuna, MC; Joachimi, B; Korn, A; Hoekstra, H; Schmidt, SJ; Alonso, D; Singh, S; Ricci, M; Hildebrandt, H; Duncan, C; Johnston, H (Oxford University Press, 2022)
Recent works have shown that weak lensing magnification must be included in upcoming large-scale structure analyses, such as for the Vera C. Rubin Observatory Legacy Survey of Space and Time (LSST), to avoid biasing the cosmological results. In this work, we investigate whether including magnification has a positive impact on the precision of the cosmological constraints, as well as being necessary to avoid bias. We forecast this using an LSST mock catalogue and a halo model to calculate the galaxy power spectra. We find that including magnification has little effect on the precision of the cosmological parameter constraints for an LSST galaxy clustering analysis, where the halo model parameters are additionally constrained by the galaxy luminosity function. In particular, we find that for the LSST gold sample (i < 25.3) including weak lensing magnification only improves the galaxy clustering constraint on.